(3GdMeGjI GdLRGFjI ddedcjI GdYbGQjI GdNGUI (B/s - (3HQHGQI, YHO GdQMefs ((3GdEScfOQjI, eUQ (B:s (3OGQ GdacQ GdLGeYj,s, 2017)
(3jJfGhd cJGH (B((3GdMeGjI GdLRGFjI ddedcjI GdYbGQjI GdNGUI(B) (3hGdPj bGe HJCdjag (B((3GdOcJhQ HQHGQI YHO GdQMef(B) (3aj MhGdj (B(204) (3UaMI ef GdbWY GdeJhSW ehVhY (B((3GdedcjI GdYbGQjI(B) (3eSJYQVG GdeMJhjGJ GdJGdjI (B: (3GdHGH GdChd (B: (3GdedcjI GdYbGQjI GdNGUI GdeYfjI HGdMeGjI GdLRGFjI(B. (3GdaUd GdChd (B: (3GdWHjYI GdbGfhfjI ddedcjI GdYbGQjI GdNGUI(B. (3GdaUd GdKGfj (B: (3hSGFd EKHGJ GdedcjI GdYbGQjI GdNGUI(B. (3GdHGH GdKGfj (B: (3hSGFd MeGjI GdedcjI GdYbGQjI GdNGUI LRGFjG, GdaUd GdChd (B: (3JLQje GdGYJOGA GdhGbY Ydi GdCedGc GdYbGQjI GdNGUI(B. (3GdaUd GdKGfj (B: (3GdNUheI Mhd GdedcjI GdYbGQjI CeGe GdbVGA GdLRGFj(B. s
Keywords: (3GdedcjI GdYbGQjIs -- (3bhGfjf hJTQjYGJs -- (3GdLRGFQs; (3YbhO GdedcjIs -- (3bhGfjf hJTQjYGJs -- (3GdLRGFQs